Design and Build Boilers for Modernization in the Tofu Industry Using Autodesk Inventor - Feri, Feri; Isninda Yahaya, Habib Bayu; Aleihydro, Algifar Aldrinova; Prakoso, Bagus (Universitas Negeri Semarang, 2025)
Most tofu producers still use steamers as boilers, which poses a risk to tofu quality. To reduce the risks and losses caused by this, a safe boiler construction is designed according to ASME (American Society of Mechanical Engineers) design standards. This research uses a Research and Development (R&D) approach supported by software capable of analysing model characteristics. The boiler construction was designed according to the ASME (American Society of Mechanical Engineers) standard, then the boiler design was created using Autodesk Inventor and a theoretical analysis was conducted using internal pressure loads to evaluate stress and displacement in the boiler construction. The results of the study obtained the specifications for a horizontal type of boiler with an operating steam pressure of 2 bar and a design pressure 4 bar. Boiler dimensions 600 mm in diameter, 1200 mm in length. Fuel uses firewood and the maximum volume of water that can be filled in the boiler is up to 113.1 litters. The material used for the plate is 5 mm stainless steel plate 304.